A Cultural Influence on the Local Government Environment in Indonesia - Tera Triyantara HRN; Dody Kusmayadi (PT FORMOSA CENDEKIA GLOBAL, 2025)
The legacy of a centralized government system with a mindset that is formed as a result of experience so far with a centralized system of government and development includes, 1) weak supervision; 2) responsiveness in changing development approaches and strategies; 3) misalignment between policies and implementation in various areas of development; 4) the economic crisis has caused the weakening of the ability of local governments; 6) the unevenness of economic growth between regions; and 7) the powerlessness of the community in the process of social change for the improvement of welfare in various regions. In Indonesia, without excluding the factors of injustice, geopolitics, and ethnicity, there is a tendency to identify movements. Therefore, it can be said that religious and cultural differences contribute to political tensions, and can even trigger separatism. While culture is a concept that encompasses many (broad) things, it includes everything from the influence of an individual's thought process to his behavior